Integrasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam dengan Integrasi Nilai-Nilai Pesantren - Zalfa Iklil Farida; Muhammad Fahmi; Ali Mas’ud (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Islamic Religious Education in public schools situated within pesantren environments requires a learning approach capable of integrating national curriculum demands with the religious values embedded in pesantren culture. This study aims to analyze the integration of the Merdeka Curriculum into Islamic Religious Education learning with pesantren values at SMPN 3 Peterongan, a public school located in the Darul Ulum Islamic Boarding School area. This research employs a qualitative case study approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings reveal that the implementation of the Merdeka Curriculum in Islamic Religious Education is flexible and student-centered, utilizing active learning methods such as project-based learning, reflective discussions, and diagnostic, formative, and summative assessments. Classroom learning is strengthened by school activities such as early-morning Qur’anic sessions, Qur’an literacy training, worship habituation, and the use of digital learning media. In addition, pesantren values are integrated through the boarding school curriculum, monthly classical book studies, gender-separated classrooms, etiquette habituation, discipline, communal cooperation, and the moral exemplification of pesantren teachers. The study concludes that integrating the Merdeka Curriculum with pesantren values results in a holistic and contextual Islamic Religious Education model. This integration not only supports academic achievement but also strengthens students’ religious character, making it a relevant and effective model for Islamic education in public schools with pesantren characteristics. Keywords: Merdeka Curriculum, Islamic Religious Education, Pesantren Value, Learning Integration, Pesantren-Based Public School